The Effect of TQM Practices on Corporate Performance and Competitive Advantage as Mediating Variable: Study at Manufacturing Companies in Makassar, South Sulawesi Province - munizu, musran (Jurnal Manajemen Teknologi, 2013)
This study conducts a comprehensive review of the literature and develops a framework that links among TQM practices, competitive advantage, and corporate performance.The paper provides empirical support for direct and indirect effects of TQM practices on competitive advantage and corporate performance.The purpose of this research is to empirically investigate the impact of TQM practices on competitive advantage and corporate performance. The study utilized primary data obtained from a questionnaire method. 167 manufacturing companies were surveyed in Makassar, South Sulawesi. A total of 114 completed questionnaires were returned as final sample. Four hypotheses have been developed through literature review and tested using Structural Equation Modeling (SEM) by software of IBM SPSS and AMOS version 20. The result shows that TQM practices has significant effect on corporate performance and competitive advantage directly. TQM practices has significant effect on corporate performance through competitive advantage. Competitive advantage has significant effect on corporate performance. Corporate performance is more influenced by competitive advantage than TQM practices.Keywords: TQM Practices, Competitive Advantage, Corporate Performance, Quality Management, Operation Management